2012
DOI: 10.1016/j.bbmt.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

EBMT Risk Score Predicts Outcome of Allogeneic Hematopoietic Stem Cell Transplantation in Patients Who Have Failed a Previous Transplantation Procedure

Abstract: Increasing numbers of allogeneic hematopoietic stem cell transplantation (allo-SCT) are being performed for patients who have failed a previous allogeneic or autologous SCT. We investigated whether the EBMT risk score could predict outcome after a subsequent allo-SCT. We analyzed prognostic factors in 124 consecutive patients who underwent a second transplantation using an allogeneic donor at our institution. Patients with either a first autologous (N = 64) or first allogeneic (N = 60) SCT were included. Age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
1
14
0
3
Order By: Relevance
“…In the present study this EBMT score predicted highly significantly the OS and NRM. Rezvani et al 21 reported in their study on second transplantations in 124 patients who had failed a previous transplantation procedure (approximately half allogeneic, half autologous) that the EBMT risk score significantly predicted the outcome, whereas in the study of Christopeit et al 13 this score had no significant predictive value for survival.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study this EBMT score predicted highly significantly the OS and NRM. Rezvani et al 21 reported in their study on second transplantations in 124 patients who had failed a previous transplantation procedure (approximately half allogeneic, half autologous) that the EBMT risk score significantly predicted the outcome, whereas in the study of Christopeit et al 13 this score had no significant predictive value for survival.…”
Section: Discussionmentioning
confidence: 98%
“…13 Due to small patient numbers in respective subgroups, valid statistical proof supporting or declassing the concept of changing the donor for individuals who had been in remission for a long time, who had not experienced GvHD after allo-HSCT1 and who do reach CR before allo-HSCT2 is lacking. The European Society for Blood and Marrow Transplantation (EBMT) risk score 14 at allo-HSCT2 was found to be of prognostic impact in several studies, 13,15 excluding our own. 10 There still is considerable debate on the impact of the conditioning regimen chosen.…”
mentioning
confidence: 74%
“…De modo geral, os estudos que utilizaram o escore de risco pré-transplante do EBMT mostraram que idade avançada, estágio da doença na fase tardia, tempo do diagnóstico para o transplante superior a 12 meses, regime de condicionamento mieloablativo, transplante alogênico, doador não aparentado, combinação de sexo do doador feminino e receptor masculino, são variáveis que contribuem para menor SG e maior MRT (9,37,39,(60)(61)(62) .…”
Section: Mortalidade No Tcth: Taxa E Preditoresunclassified
“…O zero representa melhor prognóstico pós-transplante e o cinco ou sete, pior prognóstico (4,36,37,41,59,61) .…”
Section: O Escore De Risco Pré-tcth Do European Group For Blood Marrowunclassified
See 1 more Smart Citation